Prosecutorial Discretion in Three Systems: Balancing Conflicting Goals and Providing Mechanisms for Control - Beale, Sara Sun (2014)
In regulating the authority and discretion exercised by contemporary prosecutors,national systems balance a variety of goals, many of which are in tension or direct conflict. Forexample, making prosecutors politically or democratically accountable may conflict with theprinciple of prosecutorial neutrality, and the goal of efficiency may conflict with accuracy. National systems generally seek to foster equal treatment of defendants and respect for theirrights while also controlling or reducing crime and protecting the rights of victims. Systems thatrecognize prosecutorial discretion also seek to establish and implement policy decisions aboutthe best ways to address various social problems, priorities, and the allocation of resources. Finally, all national systems are facing the challenge of increasing caseloads. The United States differs from France and Germany in the training and selection of prosecutors, in the understanding of their role, and in the structure of prosecutorial authority. This chapter explores how these differences affect the balance each system has struck among the competing goals of accountability, neutrality, efficiency, accuracy, and equal treatment, how these systems differ in the availability of mechanisms to establish and implement policies, and how each is responding to the challenges of increasingly heavy caseloads. This chapter begins with a description of the U.S. approach to the structure of prosecutorial authority, the training, selection and ethos of U.S. prosecutors, and the scope of prosecutorial discretion in the U.S. Part II turns to a comparison of the French and German systems. On the basis of this foundation, Part III then considers how the three systems are resolving some of the key tradeoffs between the goals of efficiency, accuracy, democratic accountability, neutrality, consistency, and the need for mechanisms to set priorities and policies. It concludes that the structure of prosecutorial authority is continuing to play a significant role in each system’s distinctive response to prosecutorial discretion. In contrast, differences in the traditional understanding of the prosecutor’s role seem to be of diminishing importance as each system responds to the pressure of increasing caseloads